ETHICS OF ADVERTISEMENT IN DENTISTRY- A CROSS-SECTIONAL SURVEY - Shradha Jalan; Dr. Gheena .S; Dr. R. Gayathri (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The opinions on ethics of dentistry is divided with dental practitioners agreeing on certain ethical correctness of practices and need for advertising to impact the clientele.The study aims to create awareness on ethics of advertisements related to individual dental practices or a chain of clinics or multispecialty clinics.A questionnaire was distributed through an online google forms link to about 100 people.The study population were asked to fill out the online form after reading each question thoroughly. The results were collected and the data was analysed using SPSS version 20. Descriptive statistics were expressed by means of frequency and percentage.This study concludes that students and dental practitioners are well aware of the ethics of advertising in the field of dentistry though they are divided on the intricate details and moral principles governing the need for advertising and may benefit from the institution of a national ethical committee for consult regarding the same. It could very well be a welcome initiative.